Assessing Study Quality in Meta-Analysis. (29th April 2020) - Feeley, Thomas Hugh
Abstract: An assumption of meta-analyses is made with regard to the quality of the primary studies included for analysis. Specifically, the process assumes each study is a valid estimation of a hypothesized relationship of interest. In instances when a primary study's quality is below an acceptable standard, one option is for the study be excluded from further analyses. Alternatively, studies of acceptable merit could be further investigated through moderator analyses in an attempt to explain heterogeneity among effect sizes due to quality elements. The current essay discusses methods for evaluating study quality before proposing guidelines for their assessment. It is recommended that future meta-analyses in communication include a dedicated section detailing how study quality is addressed when reviewing studies for inclusion.